Surgery for Pancreatic Cancer Liver Metastases. Navigating Uncharted Territory - Zanini, Nicola; Lombardi, Raffaele; Masetti, Michele; Fabbri, Carlo; Fornelli, Adele; Baccarini, Paola; Fiscaletti, Marta; Cennamo, Vincenzo; Jovine, Elio (JOP. Journal of the Pancreas, 2012)
Context Studies on kinetics of metastases revealed that pancreatic cancer should be considered a systemic disease at the time of diagnosis, regardless of tumor stage at imaging. Surgery is generally not indicated for metastatic pancreatic cancer because it is supposed not to improve survival. Objective Is metastasis from periampullary cancer an absolute contraindication to surgery? Could someone benefit from liver resection? Who? Methods Our prospectively collected database (2003-2012) lists 20 patients who underwent liver resection for metastases from periampullary, non-endocrine cancer. Generally, resection was offered in young patient, fit for surgery, with few metastases. Fourteen patients were affected by synchronous metastases and they underwent simultaneous pancreatectomy and liver resection, 6 patients experienced metachronous metastases. Results Median age was 60 years (IQR: 52-65 years). Pancreatic ductal carcinoma was the primary tumor in 15 patients, the remaining patients were affected by ampullary carcinoma or distal bile duct carcinoma. One right hepatectomy, 2 bisegmentectomies and 17 atypical resections were performed. Simultaneous liver and pancreatic resections did not improve postoperative morbidity and mortality if compared to standard pancreatic resections. Median follow-up was 47 months. Median overall survival (OS) was 15 months (95%CI: 8-22 months). Median OS in patients with synchronous metastases was 12 months (95%CI: 7-17 months). Median OS in patients with metachronous metastases was 28 months (95%CI: 2-55 months) from liver resection, 38 months from pancreatectomy. Conclusion Surgery for liver metastases from periampullary tumors is a minefield. It is a wrong step for most patients and death may occur even earlier if compared to palliative cure. However, a small group of patients could benefit from surgery and find a path to long-term survival.